2022
DOI: 10.3389/fimmu.2022.1070379
|View full text |Cite
|
Sign up to set email alerts
|

Markers of blood-brain barrier disruption increase early and persistently in COVID-19 patients with neurological manifestations

Abstract: BackgroundCoronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 infection is associated with disorders affecting the peripheral and the central nervous system. A high number of patients develop post-COVID-19 syndrome with the persistence of a large spectrum of symptoms, including neurological, beyond 4 weeks after infection. Several potential mechanisms in the acute phase have been hypothesized, including damage of the blood-brain-barrier (BBB). We tested weather markers of BBB damage in association with ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 62 publications
3
47
0
Order By: Relevance
“…Recent clinical studies have reported that SARS-CoV-2 causes neurological manifestations by neuroinvasion via blood brain barrier disruption [43]. For instance, an increase of TGFβ and oxidative stress were associated with pTau pathogenesis, in the Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Recent clinical studies have reported that SARS-CoV-2 causes neurological manifestations by neuroinvasion via blood brain barrier disruption [43]. For instance, an increase of TGFβ and oxidative stress were associated with pTau pathogenesis, in the Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Of note, a significant reduction in plasmatic GFAP was observed in HSL groups at 6 and 12 h post CA. While traditionally considered a marker of astrogliosis, blood GFAP levels have been suggested to reflect disruption of the blood brain barrier, both in acute CNS injury [26]and in highly inflammatory conditions such as COVID-19 [27] Indeed, GFAP is a key constituent of the astrocytic endfeets enveloping the blood brain barrier (BBB), which when damaged may release GFAP directly in the bloodstream. A reduction in BBB damage following treatment may thus underpin the neuroprotective effects of HSL.…”
Section: Discussionmentioning
confidence: 99%
“…Endotheliopathy has been also shown in PACS [377] , [378] . Disturbances of the blood-brain barrier integrity were found during COVID-19 [379] , [380] , [381] and after COVID-19 vaccination [382] , [383] , [384] .…”
Section: Sars-cov-2 Infection- and Covid-19 Vaccination-induced Syndr...mentioning
confidence: 93%